2023
DOI: 10.1093/mnras/stad833
|View full text |Cite
|
Sign up to set email alerts
|

Global N-body simulations of circumbinary planet formation around Kepler-16 and -34 analogues I: Exploring the pebble accretion scenario

Abstract: Numerous circumbinary planets have been discovered in surveys of transiting planets. Often, these planets are found to orbit near to the zone of dynamical instability, close to the central binary. The existence of these planets has been explained by hydrodynamical simulations that show that migrating circumbinary planets, embedded in circumbinary discs, halt at the central cavity that is formed by the central binary. Transit surveys are naturally most sensitive to finding circumbinary planets with the shortest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 124 publications
1
2
0
Order By: Relevance
“…In Figure 10 Lee & Chiang (2016) suggest that planets with such low density might have migrated from a distant region where the disk is cool and has low opacity, enabling efficient cooling of the accretion and forming a massive envelope even with a low-mass core. This hypothesis aligns with the general picture that most observed CBPs may have undergone migration during their formation process (e.g., Pierens & Nelson 2013;Coleman et al 2023aColeman et al , 2023b, due to the local low growth rate of planetary cores near the stability limit, which hinders the in situ formation of CBPs (Pierens et al 2020(Pierens et al , 2021.…”
Section: Discussionsupporting
confidence: 86%
“…In Figure 10 Lee & Chiang (2016) suggest that planets with such low density might have migrated from a distant region where the disk is cool and has low opacity, enabling efficient cooling of the accretion and forming a massive envelope even with a low-mass core. This hypothesis aligns with the general picture that most observed CBPs may have undergone migration during their formation process (e.g., Pierens & Nelson 2013;Coleman et al 2023aColeman et al , 2023b, due to the local low growth rate of planetary cores near the stability limit, which hinders the in situ formation of CBPs (Pierens et al 2020(Pierens et al , 2021.…”
Section: Discussionsupporting
confidence: 86%
“…Planets can be ejected from their hosts by dynamical interactions with other (mostly giant) planets (Rasio & Ford 1996;Weidenschilling & Marzari 1996;Lin & Ida 1997), by stellar flybys (Malmberg et al 2011), or by the post-MS evolution of their hosts (Adams et al 2013). Coleman et al (2023) simulated the circumbinary planetary systems for Kepler-16 and Kepler-34 and found that such systems may eject 6.3 and 9.3 planets on average, respectively, and most of these have masses smaller than Neptune. However, there are very few or almost no studies on the prediction for the number of the ejection of the Earth-to-Neptune-mass planet population because the abundance of such planets in less tightly bound wide orbits is not well known.…”
mentioning
confidence: 99%
“…Pierens et al, 2021). Development of population synthesis models of these types of systems (Coleman et al, 2023) will allow comparison with PLATO data, constraining theories of planet formation in diverse environments.…”
Section: Constraints On Planet Formation and Evolutionmentioning
confidence: 99%